Rethinking Peace : Discourse, Memory, Translation, and Dialogue - Hinton, Alexander Laban; Shani, Giorgio, 1970-; Alberg, Jeremiah, 1957- (Critical perspectives on religion in international politics., 2019)
This edited volume critically interrogates the field of peace studies, considering its assumptions, teleologies, canons, influence, enmeshments with power structures, biases, and normative ends.